Defense inductors in the control of mildew (Peronospora variabilis Gaum.) in the quinoa crop: Detection, epidemiology, symptoms, characteristics and control - Aguilar, René (2020)
Quinoa crop (Chenopodim quinoa Willd.) is native to the Peruvian Andes, nutritious food and it has become very important for agroexport. In Piura, the downy mildew disease appeared causing economic losses, were set as objectives: detect the primary inoculum, describe the symptoms and evaluate the effect of defense inductors in the control of downy mildew. The direct detection methodology was used to observe oospores, the treatments were; Biosar, 3Tac, Agromos + Soil set, Action FP/Pare, Metalosate and control, Area Under the Disease Progress Curve (ABCPE) was evaluated, comparisons of means were made of the Tukey test (α = 0.05). Oospores were detected in all the quinoa samples, being with greater number the var. INIA-altiplano with 96 and with lower var. passankalla with 8 oospores/100 units of seed. As a symptom, yellowish spots were observed on the upper side and gray sporulation on the underside of the leaves. The highest value of ABCPE was obtained by the control with 2,161.02; the lower values and that better controlled the mildew disease in quinoa, they were obtained with Action FP/Pare (0.5 / 0.5 L / 200L water) and Agromos + Soil set (0.25 + 0.25 L / 200 L water), with 939.8 and 1040.7 respectively.